PERTUMBUHAN DAN HASIL KACANG TANAH (Arachis hypogaea L.) PADA PERBEDAAN TINGKATAN KANDUNGAN AIR (Growth And Yield Of Peanuts At Different Water Level) - . Evita (Bioplantae, 2012)
This study was aimed to determine the response of peanut to some extent water, the level of water content and water needs best influence on the growth and yield of peanut crops. Experiment was arranged in a completely randomized design (CRD) with one factor, namely the provision of water that consists of five levels, namely the provision of water to the conditions of 25%, 50%, 75%, 100% and 125% field capacity. The variables measured were plant height, days to flowering, canopy dry weight, number of pods containing the number of empty pods, 100 seed weight and seed yield crop.The results showed that the water level significantly affected plant height, days to flowering, canopy dry weight, number of pods containing the number of empty pods, 100 seed weight and seed yield crop. The level of water to the 100% field capacity conditions provides growth and yield of groundnut crop was best.Key words : Peanuts, water content, water level